Further Results Concerning Delay-Dependent H∞ Control for Uncertain Discrete-Time Systems with Time-Varying Delay. (10th December 2009) - Zong, Guangdeng; Hou, Linlin; Yang, Hongyong
Abstract : This paper addresses the problem of H ∞ control for uncertain discrete-time systems with time-varying delays. The system under consideration is subject to time-varying norm-bounded parameter uncertainties in both the state and controlled output. Attention is focused on the design of a memoryless state feedback controller, which guarantees that the resulting closed-loop system is asymptotically stable and reduces the effect of the disturbance input on the controlled output to a prescribed level irrespective of all the admissible uncertainties. By introducing some slack matrix variables, new delay-dependent conditions are presented in terms of linear matrix inequalities (LMIs). Numerical examples are provided to show the reduced conservatism and lower computational burden than the previous results.